The Effect of Educational Religious Intervention on Improving Life Expectancy in Cancer Patients Undergoing Chemotherapy: A Randomized Controlled Clinical Trial - Mehran Naghibeiranvand; Razia Mohseni; Ghazal Shafieian (علوم بهداشتی ایران)
Background and Purpose: The main problem of cancer patients is the feeling of despair and hopelessness. Religious beliefs can boost the morale of cancer patients. This study aimed to determine the effect of religious interventions on life expectancy in cancer patients undergoing chemotherapy. Materials and Methods: The present clinical trial study was conducted on 128 patients with cancer undergoing chemotherapy referred to the oncology unit of a teaching hospital in Khorramabad, Iran. After selecting the sample size, the patients were randomly divided into intervention and control groups. In addition to routine care, religious intervention sessions were performed for the intervention group, and the control group received only routine care. For the intervention group, training sessions focused on trust in God, good morals, patience, gratitude, and remembrance of God. After 3 weeks and 6 sessions (after finishing the sessions), the post-test was done. Data collection tools were the demographic and Miller’s standard life expectancy questionnaires. Analysis of covariance was used to compare life expectancy after the intervention. SPSS software, version 23 was employed for data analysis. A significance level of 0.05 was considered for all tests. Results: There were 64 men and 64 women in both groups. Also, 111 people were married in both groups. The most frequent cancer seen in both intervention and control groups was gastric cancer (n=37). The mean life expectancy scores of the experimental and control groups before the intervention were not statistically significant (P<0.05). There was a statistically significant difference in life expectancy scores before and after the intervention in the experimental group (P<0.05). There was a statistically significant difference in life expectancy scores after the intervention in the experimental and control groups (P=0.000). Conclusion: Religious intervention increases the life expectancy of cancer patients undergoing chemotherapy. Medical staff, especially nurses, can, along with other routine care, guide patients undergoing chemotherapy to spirituality and help them accept the disease and its complications better.